2022
DOI: 10.1038/s41467-022-33393-8
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity in self-powered artificial striate cortex for binocular orientation selectivity

Abstract: Get in-depth understanding of each part of visual pathway yields insights to conquer the challenges that classic computer vision is facing. Here, we first report the bioinspired striate cortex with binocular and orientation selective receptive field based on the crossbar array of self-powered memristors which is solution-processed monolithic all-perovskite system with each cross-point containing one CsFAPbI3 solar cell directly stacking on the CsPbBr2I memristor. The plasticity of self-powered memristor can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…15 ); this phenomenon is called paired-pulse facilitation (PPF), which is a typical form of short-term synaptic plasticity 40 . The PPF index 41 demonstrates that the passivated perovskite layer has a slow attenuation (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…15 ); this phenomenon is called paired-pulse facilitation (PPF), which is a typical form of short-term synaptic plasticity 40 . The PPF index 41 demonstrates that the passivated perovskite layer has a slow attenuation (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing to the standard paired-STDP, triplet-STDP contains a third spike either presynaptic or postsynaptic. [59,[67][68][69] The relationship between the paired term and triplet term contributions provides the multiplicative correlations between presynaptic and postsynaptic activities. Therefore, triplet-STDP possesses advantages over pair-STDP to demonstrate spiking rate-based synaptic plasticity, such as rate-based Bienenstock-Cooper-Munro (BCM) learning rule and high-order spatiotemporal processing function.…”
Section: Resultsmentioning
confidence: 99%
“…The problems of motion detection and activity recognition are still beyond the reach of current machine vision systems, and classical computer vision still faces enormous challenges. Ren et al reported a self-powered perovskite photoelectric memristor with a two-terminal structure, and the device structure is shown in Figure a . This work not only realizes optical-encoded pattern recognition but also has great significance for machine vision used in detection functions.…”
Section: Research Progressmentioning
confidence: 99%
“…(e) The schematic representation of binocular orientation selectivity; directional preference receptive field development in the human visual system based on the Bienenstock–Cooper–Munro (BCM) rate-based theory. Reproduced with permission from ref . Copyright 2022 Nature Publishing Group.…”
Section: Research Progressmentioning
confidence: 99%